Usability of Mobile Health Application for Individuals with Type 2 Diabetes Mellitus and Clinicians - TİMURTAŞ, EREN; POLAT, MİNE GÜLDEN (MARMARA UNIV, INST HEALTH SCIENCES, 2020)
Objective: Usability of technological devices is an important and relevant construct as mobile technologies are increasingly used to deliver healthcare products. Most accessible devices are smartphone and smartwatch but information on their usability is scarce. The aim of this study is to compare the usability of smartphone and smartwatch devices in delivering an exercise platform to individuals with Type 2 Diabetes Mellitus (T2DM) among two focus groups: individuals with T2DM and clinicians. Methods: A total of 40 individuals with T2DM (focus group 1) and 20 clinicians (focus group 2) were recruited to use the platforms one week. Each focus group was randomly divided into: smartphone and smartwatch groups. Each participant was provided with a practice trial for a week before data collection. Usability of both devices was measured with System Usability Scale (SUS). Student t-test was used to compare the total and subscale scores of SUS between two devices in each focus group. Results: In focus group 1 and 2, the mean total scores of SUS were slightly higher in smartphone group (88,75 +/- 9,34 and 86,75 +/- 8,68 ) than smartwatch group (87,87 +/- 7.56 and 82,35 +/- 6,59) respectively. When compared to individual items, three items were statistically significant in focus group 1 and one in focus group 2 (p <= 0.05). Conclusion:This study demonstrates a high usability (SUS score>80,8) for both smartphone and smartwatch devices in individuals with T2DM and clinicians. When compared between devices for two groups, exercise platform delivered through smartphone performed better on usability than smartwatch for both individuals with T2DM and clinicians.
Keywords: Type 2 Diabetes Mellitus; Mobile Health; Smartphone; Technology; SELF-MANAGEMENT; TECHNOLOGY; SYSTEM; SUS